2005
DOI: 10.1002/cbf.1190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-lipoic acid supplementation on markers of protein oxidation in post-mitotic tissues of ageing rat

Abstract: In the present study, we investigated whether DL-alpha-lipoic acid (LA) supplementation could have prooxidant or antioxidant effects on oxidative protein damage parameters such as protein carbonyl (PCO), nitrotyrosine (NT), advanced oxidation protein products (AOPP), and protein thiol (P-SH), as well as oxidative stress parameters such as total thiol (T-SH), non-protein thiol (Np-SH), and lipid hydroperoxide (LHP) in the brain and the skeletal muscle tissue of aged rats. PCO, and NT levels were increased, AOPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(92 citation statements)
references
References 41 publications
0
91
0
1
Order By: Relevance
“…Kayali et al [93] found that LA administration caused an increase in protein carbonyl and nitrotyrosine levels and a decrease in total thiol, non-protein thiol, and lipid hydroperoxide levels in the brain tissue of aged rats. The authors assumed prooxidative effects of LA in the brain tissue of aged rats may be due to the prooxidant effects of LA [93]. However, the results should be further confirmed with more convincing parameters and methods.…”
Section: Antioxidant Defensementioning
confidence: 98%
“…Kayali et al [93] found that LA administration caused an increase in protein carbonyl and nitrotyrosine levels and a decrease in total thiol, non-protein thiol, and lipid hydroperoxide levels in the brain tissue of aged rats. The authors assumed prooxidative effects of LA in the brain tissue of aged rats may be due to the prooxidant effects of LA [93]. However, the results should be further confirmed with more convincing parameters and methods.…”
Section: Antioxidant Defensementioning
confidence: 98%
“…Advanced oxidation protein product (AOPP) levels were determined according to the method of Kayali et al (2006). Briefly, 0.4 ml of lung extract supernatant was treated with 0.8-ml phosphate buffer (0.1 M; pH 7.4).…”
Section: Aopp Levelsmentioning
confidence: 99%
“…Tissue samples (200 mg) were homogenized manually in 2 ml of homogenizing bu er (100 mM KH2PO4-K2HPO4, pH 7.4, plus 0.1% (w/v) digitonin) in a glass homogenizer to avoid disruption of nuclear membranes. In this way, contamination by nucleic acids was minimized [12]. Homogenates obtained from the rats were centrifuged at 5000 × g for 10 min, and the various analytes were assayed using the supernatant fraction.…”
Section: Preparation Of Tissue Samplesmentioning
confidence: 99%